Lecturers’ Professionalism: Reflective Experiences among Islamic State Universities in West Sumatera - Trinova, Zulvia; Kustati, Martin (Universitas Islam Negeri Raden Intan Lampung, 2019)
Engagement for lecturer in Tridharma Perguruan Tinggi (Three Principles of Higher Education) across the higher education has been widely investigated. However, the professional lecturer implementation had not shown practical packaging and could not reach all the skills that gift practically needed in the higher education role. The study aim is to describe the professionalism development of lecturers of Islamic higher education institutions in West Sumatera, Indonesia from the aspects of education, research, and community services, as constituted in the Tridharma Perguruan Tinggi. Descriptive quantitative research method was used where the data taken from questionnaire and documentation. The population of the study includes 616 lecturers spreading from three Islamic state universities, with a sample of 62 lecturers. The finding showed that the professionalism development of the lecturers was done by designing lesson plans, pursuing doctoral education, attending conferences and workshops, involving students in community activities, and filling for intellectual property rights on their research. This indicates that the education and teaching, research and service can be used as a means of developing professional lectures at Islamic higher education institutions.